Exercise Testing of Adolescents and Young Adults With Sickle Cell Disease: Perceptual Responses and the Gas Exchange Threshold. (September 2019) - Ameringer, Suzanne; Elswick, R. K.; Sisler, India; Smith, Wally; Lipato, Thokozeni; Acevedo, Edmund O.
For individuals with sickle cell disease (SCD), mild to moderate exercise is advised, but self-regulation of these intensities is difficult. To regulate intensity, one SCD recommendation is to stop exercising at the first perception of fatigue. However, perceived effort and affect (how one feels) are perceptual cues that are commonly used to guide exercise intensity. This study (a) examined perceived effort, affect, and fatigue in relation to metabolic state (gas exchange) in adolescents and young adults (AYAs) with SCD, (b) explored guidelines AYAs use to self-regulate exercise, and (c) compared perceived effort and affect at gas exchange threshold (GET) with healthy counterparts. Twenty-two AYAs with SCD completed an incremental cycle test. Perceived effort, affect, and fatigue were assessed every 2 minutes. A mixed-effects linear model was conducted to model changes in effort, affect, and fatigue across time. Mean scores of effort and affect at GET were compared with published data of healthy counterparts. Participants were queried about self-regulation exercise strategies. Findings indicated that both perceived fatigue and effort at GET was lower than expected. Perceived effort was lower ( p < .0001), and perceived affect was significantly higher ( p = .0009) than healthy counterparts. Interviews revealed that most participants (95%) do not stop exercising until fatigue is moderate to severe, and many (73%) do not stop until symptoms are severe (chest tightness, blurry vision). Nurses should review guidelines for safe exercise with AYAs with SCD. Exercise training may be beneficial to AYAs with SCD for learning how to interpret bodily responses to exercise to improve self-regulation.